Analisis Potensi Likuefaksi di Area Utara Semarang dengan Data N-SPT: Liquefaction Potential Analysis in North Semarang Using SPT Data - Wibowo, Agung Hari (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Semarang is the capital of Central Java Province located on the northern side of Java Island, directly adjacent to the Java Sea. Morphologically, Semarang is divided into two parts: upper Semarang and lower Semarang. Upper Semarang has a relatively steeper slope profile, while lower Semarang has a flatter topography. In terms of geology, upper Semarang has a rock composition in the form of volcano breccia and sandstone of Quaternary age, while in the northern part the contours tend to be flatter and the rocks are composed of breccia covered by thick alluvial. Semarang is also surrounded by three active faults (Semarang Fault, Kendeng Fault, and Lasem Fault). An earthquake with a scale of M 5.6 occurred in Semarang in 1856, allegedly due to the activity of the three faults. Based on the data of the largest earthquake that ever occurred and the N-SPT and Bore Log taken at the research site, the potential for liquefaction in the area was found to be up to 20 m deep. Low potential for liquefaction is found at depths of 8 to 18 m, while for depths of 18 to 20 m the potential is very low. High potential is found at depths up to 8 m. Of the 8 meters with high potential for liquefaction, the saturated silty sand layer at a depth of 6 to 8 m is the segment with the highest potential for liquefaction.